Clinicopathological and prognostic significance of COX-2 in glioma patients: a meta-analysis - Jun Wang; Chenyan Xiang; Yi Cai; Ziyi Mei; Qianqian Lu; Binbin Liu; Lili Zou (Arquivos de Neuro-Psiquiatria, 2022)
Background In recent years, cyclooxygenase-2 (COX-2) has been identified as a cancer stem cell (CSC) marker in gliomas. Nevertheless, the clinical and prognostic significance of COX-2 in glioma patients remains controversial. Objective To evaluate the correlation of COX-2 with the prognosis in glioma patients. Methods Eligible studies on this subject were included, and pooled odd ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (95%CIs) were estimated. Publication bias was assessed through funnel plots, and heterogeneity and sensitivity were analyzed as well. Results In the present study, 11 articles with a total of 641 patients were included. The high expression of COX-2 in glioma patients was negatively associated with overall survival (OS) (n = 11; HR = 2.26; 95%CI = 1.79–2.86), and the subgroup analysis showed no differences in OS between Asian (n = 5; HR = 2.16; 95%CI = 1.57–2.97) and non-Asian (n = 6; HR = 2.39; 95%CI = 1.69–3.38) glioma patients. The Begg funnel plots test indicated that there was no evident risk of publication bias in the meta-analysis. Conclusion The present study suggests that COX-2 could be recommended as a useful pathological and prognostic biomarker in the clinical practice.